2018
DOI: 10.1038/s41598-018-28032-6
|View full text |Cite|
|
Sign up to set email alerts
|

Strong activation effect on a Ru-Co-C thin film catalyst for the hydrolysis of sodium borohydride

Abstract: In this work, we prepared a series of Ni foam supported Ru-Co, Ru-Co-B and Ru-Co-C catalysts in the form of columnar thin films by magnetron sputtering for the hydrolysis of sodium borohydride. We studied the activity and durability upon cycling. We found a strong activation effect for the Ru-Co-C sample which was the highest ever reported. This catalyst reached in the second cycle an activity 5 times higher than the initial (maximum activity 9310 ml.min−1.gCoRu−1 at 25 °C). Catalytic studies and characterizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Over the past years, intensive efforts were continued to tune the catalyst performances by strategies such as alloying, shape control, and support adjustment. , Also, metal catalysts based on earth-abundant elements have been investigated to develop economical catalysts. A comparative study showed that Co is more active than Fe, Ni, and Cu .…”
Section: Introductionmentioning
confidence: 99%
“…Over the past years, intensive efforts were continued to tune the catalyst performances by strategies such as alloying, shape control, and support adjustment. , Also, metal catalysts based on earth-abundant elements have been investigated to develop economical catalysts. A comparative study showed that Co is more active than Fe, Ni, and Cu .…”
Section: Introductionmentioning
confidence: 99%
“…At the lab scale, the catalyst is generally introduced into the ask containing the NaBH 4 fuel. 5,15 At the demonstrator scale, the aqueous solution is stored in a tank and pumped into a catalytic reactor when H 2 is needed. [8][9][10][11]16 Considering this design, two important comments should be made.…”
Section: Introductionmentioning
confidence: 99%